The immune landscape of high-grade brain tumor after treatment with immune checkpoint blockade - Park, Jang Hyun; Kang, In; Lee, Heung Kyu (Frontiers in Immunology, 2022)
Despite the therapeutic success of immune checkpoint blockade (ICB) therapy against multiple tumors, many patients still do not benefit from ICB. In particular, high-grade brain tumors, such as glioblastoma multiforme (GBM), have a very low response rate to ICB, resulting in several failed clinical trials. This low response rate might be caused by a lack of understanding of the unique characteristics of brain immunology. To overcome this knowledge gap, macroscopic studies of brain immunology are needed. We used single-cell RNA sequencing to analyze the immune landscape of the tumor microenvironment (TME) under anti-PD-1 antibody treatment in a murine GBM model. We observed that CD8 T cells showed a mixed phenotype overall that included reinvigoration and re-exhaustion states. Furthermore, we found that CCL5 induced by anti-PD-1 treatment might be related to an increase in the number of anti-inflammatory macrophages in the TME. Therefore, we hypothesized that CCL5-mediated recruitment of anti-inflammatory macrophages may be associated with re-exhaustion of CD8 T cells in the TME. We compared our observations in the murine GBM model with publicly available data from human patients with recurrent GBM. Our study provides critical information for the development of novel immunotherapies to overcome the limitations of anti-PD-1 therapy.